Penyuluhan Kesehatan Pencegahan Infeksi Nosokomial di Rumah Sakit Mitra Medika Tanjung Mulia - Eric Winarno; Chintami Octavia (Jurnal Nusantara Berbakti, 2025)
Nosocomial infections, acquired by patients during their stay in healthcare facilities, pose a significant challenge to service quality and cost efficiency. These infections worsen patient conditions and strain the healthcare system. In Indonesia, prevalence ranges from 10–15%, highlighting the need for effective prevention strategies. This community service program involved health education at Mitra Medika Tanjung Mulia Hospital to enhance patient and family awareness of nosocomial infection prevention. Activities included systematic planning, educational material development, and hands-on prevention training. As a result, participants' understanding increased from 45% to 85%, with compliance reaching 80%. However, challenges remain, such as limited resources and varying adherence levels. Therefore, continuous education, facility improvements, and regular evaluations are necessary to reduce nosocomial infection rates and enhance patient safety in healthcare settings.